Chinese pavilions in the early landscape gardens of Europe - Fekete, Albert; Gyori, Peter (Landscape Architecture and Art, 2021)
The image of China perceived by the Europeans in the 17th to 18th century was based on the travelogues of the travellers and missionaries. Despite the fact that the first descriptions did not include any pictures of the world, people and landscapes described, the far exotic country with its history and tangible heritage became very popular. This article deals with Chinese pavilions (pagodas, teahouses) built in the early European landscape gardens before 1750 without any architectural plans, using only sketches based on descriptions and travelogues, since in the first half of the 18th century, no relevant technical guidance was available yet. The structures reviewed started to be used frequently in European gardens and public parks from 1750’s, having an inevitable influence on the garden pavilions built from the second half of the 18th century, and indirectly to the image and character of some influential gardens in European context. Moreover, through their craggy appearance, the Chinese pavilions – as eye catchers – played an accentuated compositional and spatial role too in the European garden history.